Metaphoricity in the real estate showroom: Affordance spaces for sensorimotor shopping. (2nd January 2019) - Harrison, Simon; Fleming, David H.
ABSTRACT: This article adopts an ecological view of cognition to analyze the role of the environment in scaffolding metaphorical experience. Using ethnographic material collected from two real estate showrooms in China, we describe how each showroom setting is equipped with to-be-phenomenologically-experienced objects designed to stimulate desirable sensorimotor experiences and altered bodily states during the guided showroom tours. By analyzing the qualities of such settings and identifying the processes through which visitors become environmentally coupled—including active and passive touch in highly organized auditory, olfactory, and gustatory environs—we demonstrate how the showrooms constitute an affordance space for enacting metaphoricity through doubleness in experience. Implications for conceptual metaphor theory relating to the nature of environments and bodies are discussed.